2013
DOI: 10.1002/jmv.23527
|View full text |Cite
|
Sign up to set email alerts
|

Viable herpes simplex virus type 1 and varicella‐zoster virus in the trigeminal ganglia of human cadavers

Abstract: Human herpes simplex virus type 1 (HSV-1) and varicella-zoster virus (VZV) were isolated in the bilateral trigeminal ganglia of 12 human cadavers with no history of herpes-related symptoms within 1-5 days of death. Sixteen trigeminal ganglia were subjected to explant culture by using Vero cells, but no cytopathogenic effects (CPE) were observed. However, when another eight trigeminal ganglia were placed in a cell strainer and kept from direct contact with Vero cells during culture, CPE were clearly apparent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…HSV-1 is widespread throughout the world and establishes latency in sensory ganglia. In the study conducted by Saitoh et al (2013), the trigeminal ganglia obtained from 12 human cadavers submitted for forensic autopsy within 1–5 days of death were cultured over a layer of Vero cells in order to evaluate whether the virus in the ganglia of the cadavers could be reactivated. It was demonstrated that viable HSV-1 persists in human trigeminal ganglia for some time after death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSV-1 is widespread throughout the world and establishes latency in sensory ganglia. In the study conducted by Saitoh et al (2013), the trigeminal ganglia obtained from 12 human cadavers submitted for forensic autopsy within 1–5 days of death were cultured over a layer of Vero cells in order to evaluate whether the virus in the ganglia of the cadavers could be reactivated. It was demonstrated that viable HSV-1 persists in human trigeminal ganglia for some time after death.…”
Section: Discussionmentioning
confidence: 99%
“…As most humans are supposedly infected with multiple herpesviruses, the risk of virus reactivation and possible complications, especially if immunosuppression occurs, is significant. Multiple studies have concentrated on the presence of HSV-1, HSV-2, and VZV in cranial nerve ganglia, but there is limited data about the occurrence of EBV, CMV, and HHV-6 in these ganglia (Saitoh et al, 2013; Motani et al, 2006; Richter et al, 2009; Hill et al, 2008; Vrabec & Payne, 2001; Inoue et al, 2010; Cohrs, Barbour & Gilden, 1996; Furuta et al, 1992, 1997; Hüfner et al, 2007). The aim of this study was to determine the distribution of six different herpesviruses: HSV-1, HSV-2, VZV, EBV, CMV, and HHV-6 in trigeminal and facial nerve ganglia of the individuals who died of independent causes.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst VZV reactivation in explants of human ganglia remains elusive (Plotkin et al, 1977), it is reasonable to assume that this could be achieved, when the appropriate experimental conditions that favour this process are discovered. There is one report of VZV reactivation from human ganglia that had been removed 1-5 days post-mortem (Saitoh et al, 2013), but this observation has not been confirmed. Furthermore, only minimal amounts of VZV DNA replication, presumably an event preceding virus reactivation, have Sloutskin et al, 2013;Yu et al, 2013).…”
mentioning
confidence: 92%
“…Furthermore, both VZV and HSV are widespread human pathogens, with about 60 to 90% of the population latently infected by both viruses by adulthood (19). It has been reported that both viruses can reside latently in the same trigeminal ganglion (19)(20)(21)(22), and evidence from in situ hybridization suggests the rare presence of both HSV1 and VZV genomes in the same cells (23). However, the ability of both viruses to productively infect the same neuron has not been investigated.…”
mentioning
confidence: 99%